Edward III's household knights and the Crécy campaign of 1346. Issue 255 (17th January 2019) - Hefferan, Matthew
Abstract: The knights of the royal household were of central importance to medieval warfare. Their contributions to the wars of Edward III have, however, received only limited attention from historians. This article uses the Crécy campaign of 1346, the largest of Edward III's military campaigns, as a case study to argue that the household knights occupied a fundamental place in the raising of royal armies at this time, and offered the king a wealth of experienced captains capable of leading vital military missions as part of wider royal campaigns.